LEPTIN, GHRELIN AND NAFLD: NEW APPROACHES TO OBESITY TREATMENT - Mirzaeva A. X. (Web of Journals Publishing, 2025)
Circulating leptin levels correlate with high lipid levels in obesity, suggesting that human obesity is associated with leptin insensitivity. Leptin resistance in diet-induced obesity highlights that environmental factors can modulate leptin sensitivity. It is proposed that ghrelin and leptin act through the hypothalamic-pituitary axis as a metabolic switch. In this article, serum leptin, ghrelin levels were determined in patients with NASH to determine whether there is an association between leptin, ghrelin levels and the severity of liver steatosis or fibrosis.
Keywords: Leptin; leptin resistance, leptin-associated diseases, ghrelin, NAFLD, metabolic syndrome, obesity.